Pembelajaran Biologi dengan Metode Kartu Matrik Ingatan dan Turnamen Melalui Pendekatan Saintifik di SMA Negeri 7 Mataram - Tri Sari Wijayanti (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
This study aimed to determine the level of students’ activity during the learning biology with implementing of Memory, Matrix Cards and Tournaments methods through scientific approaches. The study was conducted at class XI IPA 4 and class XI IPA 5 semester 2 in academic year 2016/2017 with the number of students as a sample was 64 students. Students’ activity was measured through indicators: (1) the students carried out the tasks which was assigned in groups; (2) students’ willingness to ask questions on issues didn’t know yet; (3) the students didn’t concern with other difficultiesin the group; (4) students participated in answering the problem; and (5) students provided ideas or opinions. Students’ activity was measured using observation sheet in involving three (3) teachers. The data of Students’ activity observing were measured using a scale of 4 (four) with a range of 1-4 where 1 = not active, 2 = less active, 3 = active, and 4 = very active. The data which was gotten then converted into a scale of values 1-100. Students’ activity was observed when the students acquired learning biology using memory, the matrix cardand tournaments methods. The data ofstudents’ activity in each method were collected in 3 (three) meetings of each method. The results showed that the students’ activity with cards method was 76.76, with a memory matrix method was 76.14, and the tournament method was 81.8